MODEL STRATEGI KEBUDAYAAN DALAM PEMBERANTASAN KORUPSI DI INDONESIA - Santoso, Listiyono; Meyrasyawati, Dewi (Jurnal Review Politik, 2015)
This study attempts to create a cultural strategy to eradicate corruption in Indonesia. Various obstacles to eradicate the culture of corruption in Indonesia along with descriptions of cultural conditions which encourage corruption were easily found. Using a descriptive analytical technique this study tries to reveal corruptive behavior and its scope as well as find a variety of cultural problems. Massive corruption in Indonesia seems to draw us a conclusion that corruption has been the culture of our nation. As a cultural problem, corruption should be carefully addressed within the context of culture. Therefore, a firm model of anti-corruption education, which put emphasis on cultural mentality and formation of anti-corruption behavior for society, is urgently required. Such education should integrate within itself anti-corruption values, which put and see corruption as a common enemy for all. Education as such is expected to form a positive attitude and anti-corruption behavior.